Association Of Single Nucleotide Polymorphisms (Snp) In Pcsk9 Gene With Lipid Analysis Among Iban And Bidayuh Ethnic Groups In Sarawak Population. - H. H., Hood; Y. T., Siaw; S. P., Sim; H., Helmy; M. M, Aminudin (Centre for Pre-University Studies, 2015)
Objectives: Proprotein convertase subtilisin/kexin type 9 (PCSK9) gene (MIM: 603776) encoded protein that facilitates cholesterol level in blood. Known mutation in the PCSK9 gene would indicate hypercholesterolemia through gain of function resulting in Familial Hypercholesterolemia Type 3. The increased risk genetic variant: rs 12084215 of FH (Say et al, 2013) were used to indicate any correlation with performed lipid analysis with untested indigenous population in Sarawak. We are conducting a study to determine the polymorphic genotype frequencies among 2 indigenous populations, the Iban and the Bidayuh in Sarawak, thus elucidating any association with lipid analysis.